2019
DOI: 10.1111/jvim.15527
|View full text |Cite
|
Sign up to set email alerts
|

Multiple adrenocortical steroid response to administration of exogenous adrenocorticotropic hormone to hospitalized foals

Abstract: Background The hypothalamic‐pituitary‐adrenal axis regulates the response to sepsis‐associated stress. Relative adrenal insufficiency or adrenocorticotropic hormone (ACTH):cortisol imbalance, defined as a poor cortisol response to administration of ACTH, is common and associated with death in hospitalized foals. However, information on other adrenal steroid response to ACTH stimulation in sick foals is minimal. Objective To investigate the response of multiple adrenocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 40 publications
2
23
1
Order By: Relevance
“…The ACTH:cortisol is a practical tool that has been used to assess hypothalamic‐pituitary‐adrenal axis activity and adrenocortical insufficiency (RAI/CIRCI) in hospitalized foals 18,47 . Because ACTH stimulation induces androgen steroidogenesis, 4 it is not surprising that illness alters the ACTH:androgen ratios 15 . ACTH has been evaluated in reference to other steroids (progestogens and androgens) in healthy and sick foals 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ACTH:cortisol is a practical tool that has been used to assess hypothalamic‐pituitary‐adrenal axis activity and adrenocortical insufficiency (RAI/CIRCI) in hospitalized foals 18,47 . Because ACTH stimulation induces androgen steroidogenesis, 4 it is not surprising that illness alters the ACTH:androgen ratios 15 . ACTH has been evaluated in reference to other steroids (progestogens and androgens) in healthy and sick foals 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol, aldosterone, progestogens, and DHEA concentrations are elevated in sick foals and linked to disease severity, 11,[14][15][16][17][18] and their response to exogenous ACTH stimulation is associated with outcome. 4 Most studies of steroid concentrations in foals have been on single time measurements, precluding the assessment of steroid dynamics in relation to illness severity and outcome over time. Information on androgen concentrations in newborn foals is lacking, likely because they are seen as sex hormones rather than active steroids or intermediary to other endocrine factors, further underplaying their clinical measurement and relevance in healthy and sick foals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, according to a recent study, it has been observed that the experimental stimulation of this axis with ACTH is associated with the increase of cortisol, aldosterone, androstenedione, pregnenolone, 17a-OH-progesterone, and progesterone in critically ill patients compared to healthy animals. But interestingly, it was observed that in the animals that died, a decrease in cortisol and an endogenous increase in ACTH were observed, which suggested adrenocortical dysfunction [ 109 ]. This corroborates what has been stated above, first that the stimulation of cortisol decreases the response of the immune system, while second, this endocrine response has a limited response that can be depleted, which can serve as a prognostic factor in severe conditions.…”
Section: Endocrine Alterations Associated With Pain and Anxiety Improvementioning
confidence: 99%
“…It can secrete insulin in response to glucose and amino acids, and is believed to be important in regulating fetal nutrient utilization and growth 9 . However, complete maturation of the endocrine system and associated energy metabolism in the neonate is delayed 1,11‐13 . In addition, the neonatal foal has minimal hepatic fat stores, little glycogen, and little adipose tissue at birth 2,3 .…”
Section: Introductionmentioning
confidence: 99%